Scales’ validity and reliability for pain assessment. Pediatric Intensive Care Unit. Cienfuegos 2023 - Jayce Díaz Díaz; Ariel Efrén Uriarte Méndez; Zulema Sánchez Acosta; Yuliett Mora Pérez; Felicia Rodríguez Solís (Medisur)
Foundation: the assessment of pain requires the use of valid and reliable scales that allow identifying its presence, intensity and characteristics, for better management and treatment. Objective: to determine the scales’ validity and reliability for assessing pain in the Intensive Care Unit at the Paquito González Cueto University Pediatric Hospital in Cienfuegos. Methods: an instrument validation study was carried out from January to November 2023. The Wong Baker scale and the visual analogue scale were chosen; face, legs, activity, crying and consolation scale (Face, Legs, Activity, Cry and Consolability), and Pain Indicator Behaviors Scale. Linguistic and cultural adaptation, content validation, internal consistency, temporal stability, construct and criterion validity were carried out. Kendall's W concordance coefficient (content validity), Bartlett's sphericity test and Kaiser's normalization criterion (construct validity), Pearson's correlation coefficient (temporal stability) and global Cronbach's Alpha coefficient (internal consistency) were calculated. Results: the scales are understandable from linguistic and cultural analysis. Content validation with agreement coefficient of Kendall's W 0.233. Construct validity with Kaiser Meyer Olkim (KMO) 0.902 and Bartlett chi square test of sphericity = 1921.253. Temporal stability with Pearson correlation coefficient 0.827 and 0.917. Internal consistency with global Cronbach's Alpha coefficient 0.861. Conclusions: the scales reflect valid conditions and criteria in the assessment of pain in the Pediatric Intensive Care Unit.